Can a financial transaction tax prevent stock price booms? - Klaus Adam; Albert Marcet; Sebastian Merkel; Johannes Beutel (University of Mannheim, Department of Economics, 2015)
We present a stock market model that quantitatively replicates the joint behavior of stock prices, trading volume and investor expectations. Stock prices in the model occasionally display belief-driven boom and bust cycles that delink asset prices from fundamentals and redistribute considerable amounts of wealth from less to more experienced investors. Although gains from trade arise only from subjective belief dierences, introducing financial transactions taxes (FTTs)remains undesirable. While FTTs reduce the size and length of boom-bust cycles, they increase the likelihood of such cycles, therby overall return volatility and wealth redistribution. Contingent FTTs, which are levied only above a certain price threshold, give rise to problems of equilibrium multiplicity and non-existence.
urn:nbn:de:bsz:180-madoc-390243
Keywords: G12; D84; 330; financial transactions tax; Tobin tax; asset price booms